The Role of Community-Based Organisations in Compating HIV/AIDS in Kanungu District, Uganda. - Denis, Karugaba (Kabale University, 2020)
This study examined the contributions of community-based organisations in combating HIV/AIDS in Kanungu District, Uganda. The study espoused a case study design which exploited both qualitative and quantitative approaches. A sample of 118 respondents was used and respondents were selected using simple random and purposive sampling. Data was collected using questionnaires, interviews, focus group discussion and documentary review. Data was analysed using descriptive statistics such as frequencies and percentages. From the study, it was revealed that Kanungu Development Initiative is involved in provision of other health care services to HIV victims. Behavioural change counseling was also found to be another HIV/AIDS related activity done by Kanungu Development Initiatives in order to combat HIV/AIDS. Study findings revealed that the community is fully involved in all their interventions-through different avenues. First they have the intended beneficiaries, specifically the people living with HIV/AIDS who share their own experiences and pioneer preventive activities within the communities in which they live. The study also revealed that lack of adequate resources, proper management skills, collaboration and coordination with other agencies was noted as a challenge. In relation to this finding, the researcher emphasized that the organisation should embark on a series of income generating activities to overcome the challenge of over dependence on donors for funds, which are in most cases inadequate. Kanungu Development Initiative has proved that CBOs have great potential in not only educating people about the prevention of HIV/AIDS, but also in providing care and support to people living with HIV/AIDS and their families, by providing a wide range of interventions to both the people infected and affected by the pandemic. The study recommended that there was a need to establish or strengthen partnerships other service providers outside the field of HIV/AIDS to complement services provided by KADI, for example linking clients to organisations providing income generating activities like operations wealth creation, prosperity for all program, to mention but a few.